Effect of postoperative continuation of antibiotic prophylaxis on the incidence of surgical site infection: a systematic review and meta-analysis. Issue 10 (October 2020) - de Jonge, Stijn W; Boldingh, Quirine J J; Solomkin, Joseph S; Dellinger, E Patchen; Egger, Matthias; Salanti, Georgia; Allegranzi, Benedetta; Boermeester, Marja A
Summary: Background: Antibiotic prophylaxis is frequently continued for 1 day or more after surgery to prevent surgical site infection. Continuing antibiotic prophylaxis after an operation might have no advantage compared with its immediate discontinuation, and it unnecessarily exposes patients to risks associated with antibiotic use. In 2016, WHO recommended discontinuation of antibiotic prophylaxis after surgery. We aimed to update the evidence that formed the basis for that recommendation. Methods: For this systematic review and meta-analysis, we searched MEDLINE, Embase, CINAHL, CENTRAL, and WHO regional medical databases for randomised controlled trials (RCTs) on postoperative antibiotic prophylaxis that were published from Jan 1, 1990, to July 24, 2018. RCTs comparing the effect of postoperative continuation versus discontinuation of antibiotic prophylaxis on the incidence of surgical site infection in patients undergoing any surgical procedure with an indication for antibiotic prophylaxis were eligible. The primary outcome was the effect of postoperative surgical antibiotic prophylaxis continuation versus its immediate discontinuation on the occurrence of surgical site infection, with a prespecified subgroup analysis for studies that did and did not adhere to current best practice standards for surgical antibiotic prophylaxis. We calculated summary relative risks (RRs) with corresponding 95% CIs using a random effects model (DerSimonian and Laird). We evaluated heterogeneity with the χ 2 test, I 2, and τ 2, and visually assesed publication bias with a contour-enhanced funnel plot. This study is registered with PROSPERO, CRD42017060829. Findings: We identified 83 relevant RCTs, of which 52 RCTs with 19 273 participants were included in the primary meta-analysis. The pooled RR of surgical site infection with postoperative continuation of antibiotic prophylaxis versus its immediate discontinuation was 0·89 (95% CI 0·79–1·00), with low heterogeneity in effect size between studies (τ 2 =0·001, χ 2 p=0·46, I 2 =0·7%). Our prespecified subgroup analysis showed a significant association between the effect estimate and adherence to best practice standards of surgical antibiotic prophylaxis: the RR of surgical site infection was reduced with continued antibiotic prophylaxis after surgery compared with its immediate discontinuation in trials that did not meet best practice standards (0·79 [95% CI 0·67–0·94]) but not in trials that did (1·04 [0·85–1·27]; p=0·048). Whether studies adhered to best practice standards explained all variance in the pooled estimate from the primary meta-analysis. Interpretation: Overall, we identified no conclusive evidence for a benefit of postoperative continuation of antibiotic prophylaxis over its discontinuation. When best practice standards were followed, postoperative continuation of antibiotic prophylaxis did not yield any additional benefit in reducing the incidence of surgical site infection. These findings support WHO recommendations against this practice. Funding: None.